2021
DOI: 10.1177/15910199211011858
|View full text |Cite
|
Sign up to set email alerts
|

Is a small coil more effective as a finishing coil for the embolization of intracranial aneurysms? Outcomes using GALAXY G3™ MINI micro-coils as finishing coils in a single center

Abstract: Objective The purpose of this study was to compare the outcomes of coil embolization using a 0.009 inches primary outer diameter coil as finishing coil (FC) to that of 0.01 inches. Methods From February and August 2020, 131 aneurysms that performed coil embolization using FC with a second loop diameter of 1 mm, were reviewed retrospectively, conducting propensity score matching and logistic regression analysis. Angiographic results such as, occlusion grade, packing density, failure and event were compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Kim and colleagues, in a propensity-score matched analysis, investigated outcomes in patients treated with Target Nano coils vs. The Galaxy G3TM MINI micro-coil (GM; Cerenovus, Irvine, CA, United States) ( 23 ). Authors reported a safe profile for patients treated with Target Nano coils, with comparable PD to the current registry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and colleagues, in a propensity-score matched analysis, investigated outcomes in patients treated with Target Nano coils vs. The Galaxy G3TM MINI micro-coil (GM; Cerenovus, Irvine, CA, United States) ( 23 ). Authors reported a safe profile for patients treated with Target Nano coils, with comparable PD to the current registry.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 clinical sites within the United States with active IRB approval to participate in the TARGET Registry with 11 centers enrolling at least 1 patient, the median [IQR] aneurysms per clinical site was 12 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Mercy St. Vincent Medical Center, Toledo, Ohio served as the coordinating center for TARGET Nano Registry.…”
Section: Methodsmentioning
confidence: 99%